Larval development of Macrobrachium birai Lobao, Melo & Fernandes (Decapoda, Caridea, Palaemonidae), under laboratory conditions - [Anonymous] (Soc Brasileira Zoologia, Univ Federal Parana, 2005)
Macrobrachium birai Lobao, Melo & Fernandes, 1986, a native Brazilian species of freshwater shrimp, was captured along the coast of Rio Branco, Cananeia, state of Sao Paulo, Brazil. The eggs in early development were green and the average size was 0.60 x 0.43 mm. The larvae were reared in laboratory at average temperature of 25 degrees C. Macrobrachium birai has a prolonged larval development, with 15 morphological zoeal stages and the decapodito. The metamorphose was obtained in 144 days, through about 44 ecdysis. The molts occurred from two to eight days, in average of 3.3 days. The larvae of the M. birai present some morphological characteristics distinct from that of M. olfersii (Wiegmann,1836).